2009
DOI: 10.1002/cmdc.200800442
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Pharmacological Activity of a Potent Inhibitor of the Biosynthesis of the Endocannabinoid 2‐Arachidonoylglycerol

Abstract: Biosynthesis Inhibition: O-5596, a new inhibitor of the biosynthesis of the endocannabinoid, 2-arachidonoylglycerol, was synthesized and found to be potent (IC(50)=100 nM) and selective versus other proteins and enzymes of the endocannabinoid system in vitro and active in vivo at reducing food intake in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 21 publications
2
38
0
Order By: Relevance
“…Bisogno et al also developed MAFP organophosphorus analogs O-3640 and O-3841 that showed high selectivity for DAGLα over DAGLβ and other lipases but had poor potency, lack of stability, and poor cell penetrance 38 . Further medicinal chemistry studies improved upon O-3841, yielding the similarly potent O-5596 but with better bioavailability and stability in physiological buffers 40 . Interestingly, O-5596-treated mice displayed a significant decrease in ad libitum consumption of sweetened cereal, but not regular chow, compared to vehicle-treated mice.…”
Section: Generation Of Inhibitors For 2-ag Degradation and Synthesismentioning
confidence: 99%
“…Bisogno et al also developed MAFP organophosphorus analogs O-3640 and O-3841 that showed high selectivity for DAGLα over DAGLβ and other lipases but had poor potency, lack of stability, and poor cell penetrance 38 . Further medicinal chemistry studies improved upon O-3841, yielding the similarly potent O-5596 but with better bioavailability and stability in physiological buffers 40 . Interestingly, O-5596-treated mice displayed a significant decrease in ad libitum consumption of sweetened cereal, but not regular chow, compared to vehicle-treated mice.…”
Section: Generation Of Inhibitors For 2-ag Degradation and Synthesismentioning
confidence: 99%
“…In addition, the development of 'neutral' CB 1 antagonists, that do not show any significant signs of inverse agonism, has provided very promising results at the preclinical level, particularly in terms of their reversal of insulin and leptin resistance (105) . Furthermore, in the light of the fact that the increased endocannabinoid tone observed in metabolic disorders can be attributed to increased endocannabinoid biosynthesis, an alternative strategy to regulate dysregulated endocannabinoid tone in obesity might be to use DAGL inhibitors with consequent reduction in 2-AG biosynthesis (106) . Finally, changes in diet can be beneficial in preventing the onset of both obesity and other metabolic disorders.…”
Section: Endocannabinoids In Obesitymentioning
confidence: 99%
“…Throughout the review, the focus has been on compounds enhancing eCB signalling, but there are of course situations where a reduction of eCB signalling by blockade of eCB synthesis may be better (for a review, see Di Marzo 2008). Most work in this area has focussed upon identifying the eCBs involved in physiological processes such as retrograde signalling, neuronal development (see review by Oudin et al 2011), pain (Ho et al 2011; see also Gregg et al 2012) and food intake (Bisogno et al 2009a. However, blockade of eCB synthesis may also be neuroprotective in certain circumstances (Valdeolivas et al 2013).…”
Section: Discussionmentioning
confidence: 98%